Beyond Condoms Alternative Approaches to HIV Prevention - O’Leary, Ann (Springer US, 2002)
Our contemporary division of the progress of time should be delineated as B. A. E. (Before the AIDS Epidemic, i. e. , 1981) and P. A. E. Everyone keeps predicting the end of the epidemic, as Newsweek did in 1996 when combination therapy was introduced. But as far as we can tell from this vantage point, the virus continues, albeit a bit hobbled by a few drugs here and there, but moving forward nonetheless. Predictions are that over 100 million people will be infected with HIV by 2005. It is also clear that the number of people living with HIV in the US and other developed countries will continue to grow, as people with HIV live longer and better lives, but, paradoxically and perhaps as a result, the number of people acquiring HIV also continues to grow. HIV vaccines are at least 20, and perhaps 40 years away. When they do come on board, they may not prevent infection but may, instead, change the course of illness in those infected and hopefully render them less infectious. Further, the first vaccines will, in all likelihood, be less than 100% effective. The next generation of prevention strategies need to combine the best of biomedical, social, and behavioral approaches in order to protect the population. The male condom, along with reduction in the number of sexual partners or outright abstinence, have been the mainstay of HIV prevention